Notes on the genus Protohermes van der Weele (Megaloptera: Corydalidae) from Vietnam, with description of two new species - Liu, Xingyue; Hayashi, Fumio; Yang, Ding (Zootaxa, 2009)
A faunistic review of the dobsonfly genus Protohermes van der Weele from Vietnam is presented, with 13 species recorded. Amongst them, three species, Protohermes differentialis (Yang & Yang, 1986), Protohermes lii Liu, Hayashi & Yang, 2007, and Protohermes triangulatus Liu, Hayashi & Yang, 2007, are newly recorded. Two species are described as new to science: Protohermes ishizukai sp. nov. and Protohermes sinuolatus sp. nov. Neurhermes guangxiensis Yang & Yang, 1992 and Protohermes basiflavus Yang, 2004 are synonymized with Protohermes differentialis (Yang & Yang, 1986) and Protohermes striatulus Navás, 1926, respectively. A key to the Vietnamese species of Protohermes is also provided.